Legal Analysis of Acts of Default in the Rental Agreement for Heavy Equipment (Case Study of PT Dayton Borneo Sukses) - Zayyan Syafiqah Aggistri; Gunardi Lie; Moody Rizqy Syailendra Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The Civil Code explains that a lease agreement is an agreement in which one party will bind himself to provide the other party with the enjoyment of an item for a certain period of time by paying a price that both parties have mutually agreed upon in the agreement. However, in practice in the field, lessees often default in fulfilling lease agreements, such as defaults on delays in returning heavy equipment leased objects. The purpose of this study is to explain the forms of performance in heavy equipment rental agreements. In this study, in obtaining data, a literature study was carried out to obtain secondary data by studying the laws and regulations on books and theories related to lease agreements. The results of the study show that the forms of Default in heavy equipment leasing are delays in returning heavy equipment which is the object of leasing in an agreement. Settlements carried out as a result of a default in the lease agreement are pursued by litigation in accordance with the provisions of the applicable laws and regulations and the party committing the default must pay compensation.